Investigation of diverse polyubiquitin chains in the mouse brain using ubiquitin binding domains - Zakoko, Ahmed Mahmoud (2014)
Abstract Ubiquitination is a post-translational modification of protein by ubiquitin (Ub) and plays a vital role in the regulation of a number of cellular functions, including protein degradation via the ubiquitin proteasome system (UPS). These functions require recognition of specific ubiquitinated substrates by ubiquitin binding proteins (also known as ubiquitin receptors), which possess ubiquitin binding domains (UBDs) that interact directly with monoubiquitin and/or polyubiquitin chains. There are at least 16 different UBDs to date of which the ubiquitin associated domain (UBA) is an example. Unanchored polyubiquitin chains are a relatively new phenomenon. Studies suggest that these may be involved in the regulation of innate immunity, stress response and aggresome formation and disassembly. The level of unanchored polyubiquitin chains may be controlled by the action of specific ubiquitin ligases that synthesise them, e.g. E2-25K, or deubiquitinating enzymes that release unanchored polyubiquitin chains from polyubiquitinated substrate proteins, e.g. Isopeptidase T (IsoT). Major neurodegenerative diseases such as Alzheimer’s and Parkinson’s diseases are characterized by selective neurodegeneration and the formation of protein inclusions containing misfolded and aberrant proteins, and ubiquitin. UPS impairment has been implicated in the cause or progression of neurodegenerative disease. This thesis investigates the interaction of five different UBDs to synthetic ubiquitin; UBA of p62 and ubiqulin1 (UQ1), coupling of ubiquitin conjugation to endoplasmic reticulum degradation (CUE) of Vsp9, ubiquitin binding to ABIN and NEMO (UBAN) of NEMO and zinc finger domain (ZnFUBP) of IsoT. These studies are followed by investigating a mouse model of neurodegeneration caused by conditional genetic 26S proteasomal deletion in mouse forebrain neurons that shows accumulation of ubiquitin. I show in this thesis that the UBDs have different ubiquitin-binding properties. The p62 UBA and Vps9 CUE domains have similar binding affinity to ubiquitin; binding Lys48- and Lys63-linked, and linear polyubiquitin chains, but not to monoubiquitin. The UBAN domain of NEMO binds only to linear polyubiquitin chains. The IsoT ZnFUBP domain, which interacts with the C-terminus of proximal ubiquitin, only binds to unanchored/free ubiquitin. UQ1 did not show differential binding and bound to all species of ubiquitin investigated. Given the limited studies investigating linear and free chains in vivo, I used the UBAN domain of NEMO and the ZnFUBP domain of IsoT to investigate the abundance of linear and unanchored polyubiquitin chains respectively in the mouse brain cortex of control and 26S proteasome-deleted mice. Although I did not detect the presence of linear polyubiquitin in my studies, I demonstrate accumulation of unanchored polyubiquitin chains in the cortex and cortical mitochondria of 26S proteasome-depleted mice. I suggest that the accumulation of unanchored polyubiquitin chains in this mouse model may be due to increased de novo synthesis, disassembly of polyubiquitin chains from polyubiquitinated proteins by the action of deubiquitinating enzymes or inhibition of their degradation by the 26S proteasome. Further investigations of IsoT/USP5 and E2-25 levels did not show any significant differences that may explain the accumulation of unanchored polyubiquitin chains following 26S proteasome impairment. However, I show significantly decreased levels of p-TAK1 in the 26S proteasome-depleted mice compared to controls that will be further investigated in the future.